Case Report: A successful case of allogeneic stem cell transplantation for pediatric XMEN characterized by neutropenia - Tian, Jieyu; Zheng, Jie; Qin, Maoquan; Mao, Huawei; Zhu, Guanghua (Frontiers in Immunology, 2026)
XMEN disease (X-linked immunodeficiency with magnesium defect, EBV infection, and neoplasia) is a rare Inborn Error of Immunity (IEI)characterized by impaired magnesium ion transport due to mutations in the MAGT1 gene, which subsequently affects immune cell function. Timely diagnosis and prompt intervention are essential for improving patient outcomes. Allogeneic hematopoietic stem cell transplantation (HSCT) offers a potential therapeutic approach to restore MAGT1 function. We report an infant with XMEN who acquired a novel mutation in the MAGT1 gene, presenting recurrent severe skin infections and neutropenia after 6 months of age, which was effectively managed following aggressive anti-infective treatment and HSCT.